PENGARUH EXPERIENTIAL MARKETING DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (STUDI PADA RESTORAN IMPERIAL RESTO DI KOTA AMBON) - Rotsmi Natalia Lopumeten; Sefnat Kristianto Tomasoa (Soso-Q : Jurnal Manajemen, 2018)
Companies must have a competitive advantage in the products they offer in order to maintain customer loyalty. To achieve the competitive advantage is by experiential marketing and customer satisfaction. This study aims to test: (1) The influence of experiential marketing on the creation of customer loyalty. (2) The influence of customer satisfaction on customer loyalty. (3) The influence of experiential marketing and customer satisfaction on customer loyalty. The population of this research is Imperial Resto Restaurant customers and samples taken as many as 115 respondents, selected by using accidental sampling technique.Collection data using questionnaire and using likert scale. Analyze using descriptive analysis method percentage and multiple regression analysis. The result of research shows that partial of experiential marketing (X1) and customer satisfaction (X2) have significant influence on customer loyalty (Y) because it has tcount value greater than ttable value and has significance value 0,000 < 0,05. Test results by using the coefficient of determination (R2) shows the number of Adjusted R2 of 0.439 or 43.9%. This means that the independent variables of experiential marketing (X1) and customer satisfaction (X2) together or simultaneously can explain the dependent variable that is customer loyalty (Y) of 43.9%, while the remaining 56.1% is explained by other variables not covered in this research.Keywords: Experiential Marketing, Customer Satisfaction, Customer Loyalty